Mycobacterium chelonae bacteraemia in a patient with myasthenia gravis receiving long-term steroid therapy. Issue 10 (21st December 2019) - Samaddar, Arghadip; Srivastava, Saumya; Khan, Salman; Tak, Vibhor; Sharma, Anuradha; Nag, Vijaya Lakshmi; Bohra, Gopal Krishna
Abstract : Non-tuberculous mycobacteria (NTM) are ubiquitous environmental organisms found in soil and water. Infections caused by NTM are increasing with conditions ranging from harmless colonization to invasive infections, the latter being more common in immunocompromised hosts. In this report, we present a case of bacteraemia caused by Mycobacterium chelonae, a rapidly growing NTM belonging to Class IV in the Runyon classification, in a 71-year-old male with ocular myasthenia gravis undergoing treatment with oral prednisolone. Gram staining of these organisms from blood culture can be easily overlooked or confused with diptheroids. Detection of Gram-positive bacilli should prompt Ziehl–Neelsen staining to distinguish diphtheroids from rapidly growing mycobacteria in immunosuppressed patients. In addition, speciation and antimicrobial susceptibility testing are of paramount importance in such cases as there is considerable variation in the resistance patterns between different species of NTM. Line probe assay provides a rapid and reliable method for identification of NTM to the species level, which can guide treatment with appropriate antibiotics. This case report highlights the importance of early detection of such cases so as to optimize management and improve patient outcomes.